To jettison the mind: consciousness, conceivability, and the mind–body problem - Donson, Reid (The Stellenbosch Socratic Journal, 2024)
Ever since Descartes first introduced it, the mind–body problem has been the subject of much philosophical debate. I believe, however, that the key concept upon which these arguments hinge, the mind, is a nonsensical term. In this paper, I argue that the mind cannot be conceived of understandably, and that when we speak of the mind, we do not in fact know of what we speak. I begin with a brief description of the origin of the mind in Cartesian dualism, as well as an explanation of the two main opposing sides of the mind–body debate: physicalism and dualism. Thereafter, I explain my argument (inspired by AJ Ayer) as the Inconceivability Argument, which states that the mind is not conceivable in a way that makes an understandable difference in the world, and that we thus do not truly understand the mind. After addressing several potential objections, I explain the consequences that the Inconceivability Argument hold for dualism and physicalism. I conclude that dualism no longer has a place in debates about consciousness and that physicalism must narrow its definition so that it only includes measurable cognitive processes, but not subjective experience. If we wish to understand what we speak, write, and argue about, then it is necessary to jettison the concept of the mind.